1996
DOI: 10.1002/(sici)1096-9071(199605)49:1<41::aid-jmv7>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ENV V3 sequences from HIV‐1‐infected brain indicates restrained virus expression throughout the disease

Abstract: The isolation of human immunodeficiency virus type 1 (HIV-1) from the cerebrospinal fluid (CSF) of asymptomatic virus carriers suggests that the viral infection spreading to the brain occurs early during infection. The aim of the present study was to investigate whether HIV-1 infection of the brain parenchyma also occurs during the early phase of infection. We also wished to compare the degree of replication of the virus in the brain at different clinical stages associated with HIV-1 infection. With the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In infected humans, similar plasma HIV RNA levels are usually associated with rapid progression to AIDS (66). A recent report describing experimental infection of AGMs has demonstrated high-level plasma viremia and substantial replication in LN cells and PBMC at early times after experimental infection with a decline thereafter (25). In the present study, we demonstrated high levels of plasma viremia for naturally infected animals that had been infected for more than 10 years.…”
Section: Discussionsupporting
confidence: 71%
“…In infected humans, similar plasma HIV RNA levels are usually associated with rapid progression to AIDS (66). A recent report describing experimental infection of AGMs has demonstrated high-level plasma viremia and substantial replication in LN cells and PBMC at early times after experimental infection with a decline thereafter (25). In the present study, we demonstrated high levels of plasma viremia for naturally infected animals that had been infected for more than 10 years.…”
Section: Discussionsupporting
confidence: 71%
“…) invade the spinal cord. Using HIV-1 as the example, many HIV-1 variants are neurotropic (homing to the CNS) (Tyor et al, 1992) and concentrate in dorsal spinal cord (DiStefano et al, 1996). Because antiretroviral drugs used to treat HIV-1 do not cross the blood-brain barrier (VanLeeuwen et al, 1996), dorsal spinal cord infection would be expected to be unabated by current acquired immunodeficiency syndrome (AIDS) therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Among these agents is the HIV. The CNS is an early primary target of HIV invasion, because the virus and infected immunocytes appear early during the infection (Di Stefano et al 1996). The infection of the brain endothelium or choroid plexus by HIV-1 has been suggested (Moses et al 1993;Falangola et al 1995) and demonstrated for simian immunodeficiency virus (Edinger et al 1997).…”
Section: Effects Of Cocaine On Penetration Of Bbb By Hivmentioning
confidence: 99%